Reduced thermal conductivity of a Ge1−xSnx layer formed on a self-assembled Sn nanodot template. (24th October 2018) - Utsumi, Junya; Ishimaru, Tomokuni; Hayakawa, Yasuhiro; Shimura, Yosuke
Abstract: Self-assembled Sn nanodots were formed on SiO2 and the crystallinity and Sn composition of a Ge1−x Snx polycrystal formed on the Sn nanodots were evaluated. The average diameter of the Sn nanodots was 17.1 nm, and their density was 1.5 × 10 9 cm −2 . Raman spectroscopy revealed that the crystallinity of Ge1−x Snx increased from 52.29% to 86.82% as the Ge deposition temperature increased from 100 °C to 225 °C. However, agglomeration degraded the surface roughness when the Ge deposition temperature was high. By contrast, the Sn composition reduced from 12.84 to 4.78%. For both high Sn composition and a flat surface, lowering the Ge deposition temperature was found to be crucial. The impact of the crystallinity and Sn composition on thermal conductivity was investigated using the time-domain thermoreflectance method. Thermal conductivity increased with the increase in crystallinity, and it reached 2.305 W m −1 K −1 for Ge1−x Snx with a crystallinity of 86.82%. Ge1−x Snx alloy had lower thermal conductivity than that of Ge at the same crystallinity.